MOLECULAR DOCKING AND DYNAMIC SIMULATION ON PLA2, NIK, COX-2, AND IRAK-4 INHIBITORS AS ANTIPHLOGISTIC AGENTS IN ZINGIBER OFFICINALIS - H., CHAYA; L., CHAYA P.; MUDIGERE, AKSHATHA; MATHEW, JANE B.; FATHIMA, ZAKIYA; BIDYE, DURGESH PARESH; DIXIT, SHESHAGIRI (International Journal of Applied Pharmaceutics, 2025)
Objective: Zingiber officinalis (ginger) rhizomes are widely recognised for their health benefits, but the leaves, primarily used as flavouring agents, have not been explored for therapeutic potential. This study investigates the antiphlogistic properties of Z. Officinalis leaf constituents through molecular docking and dynamic simulation of 24 bioactive molecules identified via Gas Chromatography-Mass Spectroscopy (GC-MS), with a focus on pro-inflammatory gene suppression and inflammatory cell apoptosis induction. Methods: Docking studies were conducted using Schrödinger software (version 2023-1) on secondary metabolites from aqueous and methanolic extracts of Z. officinalis leaves against Cyclooxygenase-2 (COX-2), Interleukin-1 receptor-associated kinase-4 (IRAK-4), Phospholipase A2 (PLA2), and NF-kB-inducing kinase (NF-kB) targets. Physicochemical and pharmacokinetic properties were assessed with the QikProp module. MMGBSA simulations evaluated protein-ligand interactions, and molecular dynamics assessed protein adaptation under physiological conditions. Results: Compound Pterin-6-carboxylic acid exhibited an excellent docking score with the target NF-kB compared to standard Diclofenac. Compounds such as Cyclopropane pentanoic acid 2-undecyl and 14-pentyl bicyclohexyl-4-carbonamide showed docking scores of-8.586 kcal/mol and-7.759 kcal/mol, respectively, against COX-2 and IRAK-4. Cyclopropane pentanoic acid 2-undecyl also demonstrated a score of-7.279 kcal/mol against IRAK-4. MMGBSA showed consistent binding free energies, and pharmacokinetic properties were within acceptable limits. The simulation study generated the stability of the protein-ligand complex and found that Pterin-6-carboxylic acid showed a stable complex with 4UY1. Conclusion: Pterin-6-carboxylic acid and Cyclopropane pentanoic acid 2-undecyl demonstrate significant anti-inflammatory potential. These findings suggest their promise for developing anti-inflammatory drugs, though further in vitro and in vivo studies are required to confirm their therapeutic viability.